2012
DOI: 10.1093/nar/gks311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed non-coding RNAs in embryonic stem cell neural differentiation

Abstract: Protein-coding genes, guiding differentiation of ES cells into neural cells, have extensively been studied in the past. However, for the class of ncRNAs only the involvement of some specific microRNAs (miRNAs) has been described. Thus, to characterize the entire small non-coding RNA (ncRNA) transcriptome, involved in the differentiation of mouse ES cells into neural cells, we have generated three specialized ribonucleo-protein particle (RNP)-derived cDNA libraries, i.e. from pluripotent ES cells, neural progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…vtRNAs are ncRNAs found as part of the vault ribonucleoprotein complex of unknown function (Kedersha and Rome, 1986). Interestingly, vtRNAs are significantly upregulated during neural differentiation (Skreka et al., 2012), and NSun2 deficiency in humans causes neurodevelopmental symptoms (Abbasi-Moheb et al., 2012; Khan et al., 2012; Martinez et al., 2012). However, the role of site-specific loss of m 5 C in vtRNAs in the NSun2-mediated functions remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…vtRNAs are ncRNAs found as part of the vault ribonucleoprotein complex of unknown function (Kedersha and Rome, 1986). Interestingly, vtRNAs are significantly upregulated during neural differentiation (Skreka et al., 2012), and NSun2 deficiency in humans causes neurodevelopmental symptoms (Abbasi-Moheb et al., 2012; Khan et al., 2012; Martinez et al., 2012). However, the role of site-specific loss of m 5 C in vtRNAs in the NSun2-mediated functions remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rn7SK upregulation in mature neurons has been reported in in vitro experiments . Skreka et al identified differentially expressed non‐coding RNAs in neural differentiation, among them Rn7SK , which they found to be increased in mature neurons compared to neuronal progenitor cells and pluripotent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…These include differentiation and development [102], cell-death signalling [103] and cell-cycle regulation [104]. For example, the levels of non-coding RNAs including vault RNAs have been reported to be highly regulated during cellular differentiation [105]. Riboregulation could therefore represent a mechanism to modulate p62 function in this context.…”
Section: Biological Scope Of P62 Riboregulation By Vtrna1-1mentioning
confidence: 99%